Biodiesel and biogas production from Isochrysis galbana using dry and wet lipid extraction: A biorefinery approach. (February 2020) - Sánchez-Bayo, Alejandra; López-Chicharro, Daniel; Morales, Victoria; Espada, Juan José; Puyol, Daniel; Martínez, Fernando; Astals, Sergi; Vicente, Gemma; Bautista, Luis Fernando; Rodríguez, Rosalía
Abstract: Wet lipid extraction combined with residual biomass anaerobic digestion are alternatives to reduce the overall energy consumption of biodiesel production from microalgae. Solvents with different polarities have been studied to assess dry and wet lipid extraction process from Isochrysis galbana microalga. Ethyl acetate (EA) and a chloroform:methanol (CM) mixture yielded the best lipid extraction results in the dry and wet route with suitable lipid compositions. Fatty acid methyl esters (FAMEs) conversion of dry and wet extracted lipids with these solvents was performed by using both homogeneous (H2 SO4 ) and heterogeneous (resin CT 269) catalysts. FAME production from wet extracted lipids with the EA solvent using the CT-269 resin constitutes an advantageous process because it avoids the water elimination step, and the CT-269 is a heterogeneous commercial catalyst, readily to separate after reaction. Lipid-spent microalga was anaerobically digested, obtaining that waste biomass from the wet extraction with EA had the highest methane yield (310 mL CH4 /g volatile solids (VS). Energy balance analysis for FAMEs production with EA solvent (wet route) and heterogeneous catalyst yielded an energy recovery of about 80% in terms of biodiesel and biogas. Therefore, this process constitutes a promising route under an energy-driven microalga biorefinery. Graphical abstract: Image 1 Highlights: Lipid extraction form Isochrysis galbana were studied in dry and wet processes. Ethyl acetate is a promising extraction solvent for biodiesel and biogas production. Waste biomass extracted with ethyl acetate is suitable for methane production. Energy recovery of 80% is obtained in the biodiesel and biogas production.